EDITORIAL CONVENTIONS. (20th March 2014) - Unknown
Abstract : Letters have been ordered by chronology. Dates are given in Old Style, with the year taken to begin on 1 January; when the letter was originally dated in New Style, the equivalent Old Style date has been provided in the heading for consistency. Primarily the letters were given Old Style dates, either by the writer or by Anthony Bacon's secretaries, who endorsed most of his letters. Very occasionally, however, Anthony's secretaries are inconsistent as to whether they take the year to begin on 25 March or 1 January; unless there is evidence to the contrary, it has been assumed that endorsements follow the standard practice of the year beginning on 25 March, which in this edition is then altered to reflect the year beginning on 1 January. The endorsement and the date given by the letter-writer are often the same; Anne's letters reveal evidence that she expected the bearer to deliver her letter to London and return to Hertfordshire on the same day. On other occasions, the date given in the letter and the endorsement can be days apart. When there is no dating given by the letter-writer, however, then the date of endorsement has been taken as the date. Undated letters have been placed in chronological order, as far as the internal evidence allows, and the reasoning behind the decision is explained fully in the footnotes. In some cases, this has presented particular difficulties, when the internal evidence is very inexact.